Apicoplast Dynamics During Plasmodium Cell Cycle - Elaagip, Arwa; Absalon, Sabrina; Florentin, Anat (Frontiers in Cellular and Infection Microbiology, 2022)
The deadly malaria parasite, Plasmodium falciparum, contains a unique subcellular organelle termed the apicoplast, which is a clinically-proven antimalarial drug target. The apicoplast is a plastid with essential metabolic functions that evolved via secondary endosymbiosis. As an ancient endosymbiont, the apicoplast retained its own genome and it must be inherited by daughter cells during cell division. During the asexual replication of P. falciparum inside human red blood cells, both the parasite, and the apicoplast inside it, undergo massive morphological changes, including DNA replication and division. The apicoplast is an integral part of the cell and thus its development is tightly synchronized with the cell cycle. At the same time, certain aspects of its dynamics are independent of nuclear division, representing a degree of autonomy in organelle biogenesis. Here, we review the different aspects of organelle dynamics during P. falciparum intraerythrocytic replication, summarize our current understanding of these processes, and describe the many open questions in this area of parasite basic cell biology.